COSTA RICA. LUCHAS CONTRA LAS POLÍTICAS DE PRIVATIZACIÓN Y EL TRATADO DE LIBRE COMERCIO CENTROAMÉRICA-EE.UU. - Segura Ballar, Ricardo (2023)
The autor speaks about privatization attempt of Costa Rica telecommunications and tha social movements against the “energetic Combo”. A new oportunity of privatization appears on the horizon with the Free Trade Agreement (FTA) proposed by the United States in coincidence with economics of IMF and MB.Moreover, the article visualizes that the expansionist interest of United States is not only present in this trade, but in the world geopolitics changes as result of their military intervention against Afganistan and Irak.